Defining cosQ, the site required for termination of bacteriophage lambda DNA packaging. - Wieczorek, D J (2001)
Bacteriophage lambda is a double-stranded DNA virus that processes concatemeric DNA into virion chromosomes by cutting at specific recognition sites termed cos. A cos is composed of three subsites: cosN, the nicking site; cosB, required for packaging initiation; and cosQ, required for termination of chromosome packaging. During packaging termination, nicking of the bottom strand of cosN depends on cosQ, suggesting that cosQ is needed to deliver terminase to the bottom strand of cosN to carry out nicking. In the present work, saturation mutagenesis showed that a 7-bp segment comprises cosQ. A proposal that cosQ function requires an optimal sequence match between cosQ and cosNR, the right cosN half-site, was tested by constructing double cosQ mutants; the behavior of the double mutants was inconsistent with the proposal. Substitutions in the 17-bp region between cosQ and cosN resulted in no major defects in chromosome packaging. Insertional mutagenesis indicated that proper spacing between cosQ and cosN is required. The lethality of integral helical insertions eliminated a model in which DNA looping enables cosQ to deliver a gpA protomer for nicking at cosN. The 7 bp of cosQ coincide exactly with the recognition sequence for the Escherichia coli restriction endonuclease, EcoO109I.